Why Is It Unclear? Understanding Internet Texts on the Basis of Modified Receptive Experiment - Akimova, Nataliya (East European Journal of Psycholinguistics, 2015)
The article is an attempt to look at the problem of Internet communication comprehensibility with reader’s eyes. Using a modified receptive experiment (with the participation of 450 respondents) speech units have been revealed which, according to users, difficult to understand internet text. For investigation eleven announcements were selected that most fully embody the features of the Internet, Internet communication and news sites language. Readers’ projections are analyzed according to three criteria: regularity of deviant units detection by recipients (percentage of lexemes marked with respect to all of deviant speech units (DSU) for each announcement), generalization, to what parts of speech are the accented by readers deviant units belong; and comparing the detected by the recipient deviant speech units with text semantic dominants. As a result, it is found that acute deviance is traced in the nomination, to a lesser extent, among pronouns. Predicates are almost always specified in the meaning, so they do not act as deviant speech units. Deviant speech units are almost always sense dominant in news announcements. Deviant units are better perceived by readers when they understand the dominant structure of the text. Basically, the whole group of recipients can detect almost all deviant units in the texts, but the possibility is considerably limited, one person on average notices less than a quarter of deviations. Thus the readers better notice inadequate speech units, the most difficult task for him/her is to detect incongruous units. References Akіmova, N. (2014a). Variativnost’ ponimanija kak osobennost’ sovremennoj internetkommunikacii [Variability of understanding as a feature of modern Internet communication]. Russkaja filologiya. Visnyk of Hryhoriy Skovoroda National Pedagogical University of Kharkiv, 1–2(51), 34–37. Akimova, N. (2014b). Specifika rechevyh edinits, uslozhnyayushchih ponimanie teksta [The specific of speech units that impede text understanding]. Journal of Psycholinguistics, 2(20), 60–68. Belyanin, V. (2003). Psiholingvistika [Psycholinguistics]. Moscow: Flinta. Popova, Z., Sternin, I. (2003). Ocherki po Kognitivnoy Lingvistike [Outlines on Cognitive Linguistics]. Voronezh: Istoki.